ASSOCIATION OF HYPERTENSION WITH APOE4 AND LIPID PROFILE IN WOMEN WITH DIFFERENT MENOPAUSAL STATUS - Arooj, Burarah; Khurshid, Rukhshan; Hashmat, Naheed; Saleem, Mahjabeen (Pakistan Journal of Physiology, 2013)
Background: An association between ApoE4 and ApoE2 alleles with high blood pressure in relation to different menstrual phases has been observed. Objectives: To examine the association between lipid profile, ApoE polymorphism and hypertension in a group of peri- and postmenopausal women. Methods: Study included 63 hypertensive female patients having age range of 45–80 years. Patients were divided into two groups based on their menopausal status. Group A included 43 hypertensive peri- menopausal women and Group B included 21 hypertensive post-menopausal women. Thirty age-matched normal healthy subjects were taken as controls. Patients were taken from medical out-door of Sir Ganga Ram Hospital, and Services Hospital, Lahore. ApoE4 and lipid profile were measured in all subjects. Results: In peri-menopausal women E2/2 was 42% and it was 60% in postmenopausal women. E4/4 was 58% and 40% in peri- and postmenopausal women respectively. Level of serum cholesterol and the carrier lipoproteins LDL-c and VLDL-c were increased in peri-menopausal women as compared to postmenopausal women but significant difference (p<0.05) was only observed in case of LDL-cholesterol. The levels of serum triglyceride and carrier lipoprotein HDL cholesterol were decreased in peri-menopausal women compared to postmenopausal women but significant difference (p<0.05) was only observed in case of triglyceride. Conclusion: Both, peri- and postmenopausal conditions are associated with APOE genotypes and altered serum lipid profile and thus an independent risk factor for developing cardiovascular diseases especially in postmenopausal women. Pak J Physiol 2013;9(2):29–31